Fata morganas in oil-rich, institution-poor economies. (March 2019) - James, Alexander
Abstract: Oil-dependent countries suffer from bad institutions. While some believe oil to be the culprit, others have argued that institution-weak economies are poor and resource dependent as a result. This concern previously motivated examinations of resource abundance (e.g., resource production or deposits) that tend to yield different results. But this does not confirm endogeneity bias because resource abundance may not accurately capture the relative importance of natural resources to an economy. In this paper, it is demonstrated that institutional quality is indeed correlated with GDP, and that this fully explains the observed negative relationship between institutional quality and energy dependence. This finding offers broad implications that reach beyond the resource-development literature and speaks generally to the practice of scaling explanatory variables by GDP. Abstract : Highlights: Resource-dependent countries suffer from weak institutions. Resource dependence is endogenous to the overall size of the economy. Low levels of GDP imply high levels of resource dependence. Natural resources are uncorrelated with institutional quality.